2020
DOI: 10.1111/cns.13441
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a tumor electric field treatment system in a rat model of glioma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Permanent neural implants have been clinically available for multiple neurological disorders for years (50) .Simultaneously, an FDA-approved device for glioblastoma now exists (worn on the scalp, powered by a backpack battery, and applies tumor-treating fields) (8) . This is despite its mild benefit on survival in patients (8) and in rats (5.8 ± 2.7 wks median and 10% total survival) (55) . To induce hypothermia, heat must be transported out of the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Permanent neural implants have been clinically available for multiple neurological disorders for years (50) .Simultaneously, an FDA-approved device for glioblastoma now exists (worn on the scalp, powered by a backpack battery, and applies tumor-treating fields) (8) . This is despite its mild benefit on survival in patients (8) and in rats (5.8 ± 2.7 wks median and 10% total survival) (55) . To induce hypothermia, heat must be transported out of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy: Briefly, using a previously described protocol (55) , CAR T cells were generated by harvesting splenocytes from mice, and transducing them with a retrovirus that induces CAR T expression specifically targeting EGFRvIII on CT2A tumor cells. CAR T cells were stored in liquid nitrogen 4 days post-transduction.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, combined with radiotherapy [ 20 25 ], chemotherapy [ 22 , 26 – 38 ], and other treatments, TTFields obtains better therapeutic effects. As a non-invasive physical therapy, TTFields has mild adverse reactions, mostly grade 1–2 cutaneous adverse reactions such as mild to moderate rash under the electrodes [ 3 , 6 ], erythema, dermatitis, pruritus [ 2 , 4 , 9 , 10 , 14 , 15 , 19 , 39 , 40 ], erosions [ 24 , 41 , 42 ], with no or minimal grade 3 skin adverse events [ 2 , 10 , 14 ]. Reassuringly, these symptoms improve with steroid treatment, electrode replacement, or temporary cessation of TTFields [ 2 , 9 , 10 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that TTFields increase cell death through P53-dependent [ 57 ], reactive oxygen species elevation [ 30 ], caspase-dependent/independent pathways, and O 6 -methylguanine-DNA methyltransferase (MGMT)-independent pathways [ 20 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation